The English Language in Ireland:An Introduction - Kallen, Jeffrey L. (International Journal of Language, Translation and Intercultural Communication, 2012)
Irish English, as the oldest overseas variety of English, displays a number features which are unique to Ireland or which show characteristic patterns in the use of variation within English more generally. Many of these features reflect the interacting infl uences of settlement from England and Scotland, bringing with it elements from British dialects as well as elements now considered obsolete in British English, and transfer (via intergenerational bilingualism and language shift) of elements from the Irish language. Some features of this mix have continued from early times to the present, others have died out with the increasing homogenisation of Irish English, and still new elements, from internal change and other linguistic infl uences, continue to develop the language.